The Effect of Applying Blended Learning using WhatsApp Group on Students Critical Thinking Skills in Online Learning in Elementary Schools (Pre- Experimental Study of Social Sciences in The Fourth Grade of SDN Cibabat 5) - Amalia, Mila; Sapriya, Sapriya (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
This research aims to determine the effect of applying blended learning using WhatsApp Group (WAG) on students' critical thinking skills in online learning in elementary schools. The research was conducted to obtain an overview of critical thinking skills in Social Sciences subjects. The subjects of this study were 40 fourth-grade students of SDN Cibabat 5, Cimahi Utara District, Cimahi City. This type of research is pre-experimental research with a One-Shot Case Study design. The data analysis technique used statistical tests with the One-Sample t-test at the 95% confidence level. The results of the research show that the value of t-count > t-table is 3.909> 2.023, and the value of sig. (2-tailed) <0.05, that meaning there is an effect of applying blended learning using WhatsApp Group (WAG) on students' critical thinking skills in online learning in elementary schools.